Effect of colloids on non-Fickian transport of strontium in sediments elucidated by continuous-time random walk analysis. (September 2019) - Liu, Dong-Xu; Zuo, Rui; Jivkov, Andrey P.; Wang, Jin-Sheng; Hu, Li-Tang; Huang, Liu-Xing
Abstract: Understanding the influence of colloids on radionuclide migration is of significance to evaluate environmental risks for radioactive waste disposals. In order to formulate an appropriate modelling framework that can quantify and interpret the anomalous transport of Strontium (Sr) in the absence and presence of colloids, the continuous time random walk (CTRW) approach is implemented in this work using available experimental information. The results show that the transport of Sr and its recovery are enhanced in the presence of colloids. The causes can be largely attributed to the trap-release processes, e.g. electrostatic interactions of Sr, colloids and natural sediments, and differences in pore structures, which gave rise to the varying interstitial velocities of dissolved and, if any, colloid-associated Sr. Good agreement between the CTRW simulations and the column-scale observations is demonstrated. Regardless of the presence of colloids, the CTRW modelling captures the characteristics of non-Fickian anomalous transport (0 < β < 2) of Sr. In particular, a range of 0 < β < 1, corresponding to the cases with greater recoveries, reveal strongly non-Fickian transport with distinctive earlier arrivals and tailing effects, likely due to the physicochemical heterogeneities, i.e. the repulsive interactions and/or the macro-pores originating from local heterogeneities. The results imply that colloids can increase the Sr transport as a barrier of Sr sorption onto sediments herein, apart from often being carriers of sored radionuclides in aqueous phase. From a modelling perspective, the findings show that the established CTRW model is valid for quantifying the non-Fickian and promoted transport of Sr with colloids. Graphical abstract: Image 1 Highlights: Column-scale experimental data without and with colloids evaluated. Continuous Time Random Walk (CTRW) model examined for the co-transport of Sr and colloids. Quantifying of non-Fickian Sr transport in the absence and presence of colloids, and CTRW captures the regimes. Influence of physicochemical heterogeneities on migration analysed. Abstract : Quantifying of Sr anomalous transport in the absence and presence of colloids, and CTRW captures the non-Fickian regimes influenced by physicochemical heterogeneities.